Mechanomyography reflects the changes in oxygenated hemoglobin during electrically evoked cycling in individuals with spinal cord injury - Hamzaid, Nur Azah (Wiley, 2024)
Background: Functional electrical stimulation (FES) cycling has been reported to enhance muscle strength and improve muscle fatigue resistance after spinal cord injury (SCI). Despite its proposed benefits, the quantification of muscle fatigue during FES cycling remains poorly documented. This study sought to quantify the relationship between the vibrational performance of electrically-evoked muscles measured through mechanomyography (MMG) and its oxidative metabolism through near-infrared spectroscopy (NIRS) characteristics during FES cycling in fatiguing paralyzed muscles in individuals with SCI. Methods: Six individuals with SCI participated in the study. They performed 30 min of FES cycling with MMG and NIRS sensors on their quadriceps throughout the cycling, and the signals were analyzed. Results: A moderate negative correlation was found between MMG root mean square (RMS) and oxyhaemoglobin (O(2)Hb) r = -0.38, p = 0.003], and between MMG RMS and total hemoglobin (tHb) saturation r = -0.31, p = 0.017]. Statistically significant differences in MMG RMS, O2Hb, and tHb saturation occurred during pre- and post-fatigue of FES cycling (p < 0.05). Conclusions: MMG RMS was negatively associated with O(2)Hb and muscle oxygen derived from NIRS. MMG and NIRS sensors showed good inter-correlations, suggesting a promising use of MMG for characterizing metabolic fatigue at the muscle oxygenation level during FES cycling in individuals with SCI.